Influenza Vaccination Among Australian Hajj Pilgrims: Uptake, Attitudes, and Barriers. Issue 6 (21st August 2014) - Barasheed, Osamah; Rashid, Harunor; Heron, Leon; Ridda, Iman; Haworth, Elizabeth; Nguyen‐Van‐Tam, Jonathan; Dwyer, Dominic E.; Booy, Robert; on behalf of the Hajj Research Team
<x xml:space="preserve">Abstract</x> Background Hajj is the largest annual mass gathering where the risk of respiratory infection is high. Although the Saudi Arabian authority recommends influenza vaccination for Hajj pilgrims, the uptake is variable. Influenza vaccine uptake data among Australian Hajj pilgrims is not readily available. Therefore, we aimed to estimate the influenza vaccination uptake rate and identify both attitudes and barriers to vaccine uptake from two consecutives surveys at Hajj in 2011 and 2012. Methods Using an anonymous self‐administered questionnaire, surveys were conducted in Mecca, Saudi Arabia, among Hajj pilgrims from Australia in 2011 and 2012. Pilgrims staying in "Australian" tents were recruited serially. Results In 2011, 431 Australian pilgrims completed the survey—median age was 42 (range 7–86) years, 55% were male; 65% reported receiving influenza vaccine. In 2012, 535 pilgrims of median age 43 (range 12–83) years completed the survey, 62% were male; 89% reported receiving the vaccine. Both in 2011 and 2012, common reasons for not receiving the vaccine were the pilgrims' reliance on their "natural immunity" (33 and 26%, respectively, p = 0.4) and believing that they would rarely catch influenza or come in contact with influenza patients (18 and 29%, respectively, p = 0.1). In 2012, when asked why they had received the vaccine, 65% pilgrims responded that it was because of the tour group leaders' recommendation. Conclusion Influenza vaccine uptake among Australian Hajj pilgrims seems satisfactory and increasing but could be better because many pilgrims have misconceptions about vaccines. Tour operators may play a greater role in promoting vaccination.